Serum qAnti‐HBc combined with ALT and HBsAg predicts significant hepatic inflammation in HBeAg‐positive immune active patients. Issue 9 (12th May 2022) - Wang, Xiaomei; Gao, Xiuzhu; Wu, Ruihong; Chi, Xiumei; Xu, Hongqin; Guan, Yazhe; Jin, Qinglong; Niu, Junqi
Abstract: Background and Aim: Quantitative hepatitis B core antibody (qAnti‐HBc) level has been reported to predict significant liver inflammation in treatment‐naïve chronic hepatitis B patients. However, little evidence has been revealed that qAnti‐HBc alone or with other serum parameters in predicting moderate to severe hepatic inflammation in HBeAg‐positive immune active patients treated with entecavir (ETV). Methods: A total of 142 patients with HBeAg‐positive immune active hepatitis were recruited in our study. Serum liver biochemistry, qAnti‐HBc, hepatitis B virus markers, and liver inflammation were evaluated during 48‐week ETV treatment. The association between liver inflammation grades and serum markers was systematically analyzed. Results: The patients with moderate to severe inflammation (≥ G2) had a significantly higher level of qAnti‐HBc compared with those with no to mild liver inflammation patients (< G2). The levels of qAnti‐HBc and alanine transaminase (ALT) were positively correlated with hepatic inflammation grades, and qAnti‐HBc had a better correlation than ALT, whereas HBsAg was negatively correlated with hepatic inflammation grades before treatment. After 48‐week ETV treatment, no correlation was observed between hepatic inflammation grades and qAnti‐HBc, ALT, or HBsAg. The combination of qAnti‐HBc, ALT, and HBsAg had better performance in predicting significant liver inflammation (≥ G2) than qAnti‐HBc alone or its combination with ALT. Conclusion: Serum qAnti‐HBc levels were positively correlated with hepatic inflammation grades before treatment, but no positive correlation between them was observed after 48‐week treatment. The level of qAnti‐HBc combined with ALT and HBsAg may serve as a more reliable marker for identifying significant liver inflammation before treatment in HBeAg‐positive immune active patients.